Vortex-induced Vibration of a Flexible Free-hanging Circular Cantilever - R. W. Prastianto; K. Otsuka; Y. Ikeda (Institute for Research and Community Services, Institut Teknologi Bandung, 2009)
The behavior of a free-hanging riser of floating offshore structures would be different from a typical at-sea-floor-terminated riser type of oil or gas platforms. For the design purpose, the present study was intended to incorporate some important factors of the riser conditions (i.e. bidirectional vibration, freeend condition, and spanwise variation of response amplitude) for investigating its dynamics characteristics. An experimental investigation on time-dependent motion of a flexible free-hanging circular cantilever subjected to uniform crossflows has been carried out. The free-end condition cantilever has a 34.4 aspect ratio and a low mass ratio of about 1.24. The cylinder freely oscillates in both inline and transverse to the flow. Reynolds number varied from 10,800 to 37,800. The